Biologic drugs in treating allergic bronchopulmonary aspergillosis in patients with cystic fibrosis: a systematic review. (27th July 2022) - Manti, Sara; Giallongo, Alessandro; Parisi, Giuseppe Fabio; Papale, Maria; Mulè, Enza; Aloisio, Donatella; Rotolo, Novella; Leonardi, Salvatore
Background: Aspergillus fumigatus is a common saprophytic fungus causing allergic bronchopulmonary aspergillosis (ABPA) in patients with cystic fibrosis (CF). The recommended first-line treatment for ABPA is oral steroids, followed by antifungal therapy. However, both treatments are not free from adverse effects; thus, efforts are being made to identify new drugs showing the same effectiveness but with fewer or no side-effects. Therein, biologic drugs have been significantly implemented in clinical practice in treating ABPA in patients with CF. Objective: To systematically review the available literature, providing evidence for the administration of biologic drugs as a new potential treatment of ABPA in both the paediatric and adult populations with CF. Methods: A systematic review of the literature published between January 2007 and July 2021 was performed, using a protocol registered with the International Prospective Register of Systematic Reviews (PROSPERO CRD42021270932). Results: A total of 21 studies focusing on the use of biologics in treating ABPA in CF patients was included. We highlighted a paucity of data providing evidence for biologic drug use in ABPA. Conclusion: Scientific evidence is insufficient to support firm conclusions and randomised clinical trials are urgently required to investigate the efficacy and safety of biologics for ABPA in CF patients. Biologic drugs may represent a therapeutic option in allergic bronchopulmonary aspergillosis. However, randomised clinical trials are required to assess their efficacy and safety. https://bit.ly/3whnd5N